Atrial fibrillation‐linked GJA5/connexin40 mutants impaired gap junctions via different mechanisms. Issue 8 (19th March 2014) - Bai, Donglin
Abstract : The gap junctions (GJs) formed by Cx40 and Cx43 provide a low resistance passage allowing for rapid propagation of action potentials. Sporadic somatic mutations in GJA5 (encoding Cx40) have been identified in lone atrial fibrillation (AF) patients. More recently germline autosomal dominantly inherited mutations in GJA5 have been found in early onset lone AF patients in several families over generations. Characterizations of these AF‐linked Cx40 mutants in model cells and in patient tissues revealed that some of the mutants reduced GJ channel function due to an impaired trafficking or channel formation. While others showed a gain‐of‐function in hemichannels. These functional alterations in GJs or hemichannel may play an important role in the pathogenesis of AF in the mutant carriers.